Comparison between dexmedetomidine and midazolam as intranasal premedications forchildren admitted for elective surgery (Eurasian Medical Research Periodical, 2022)
The intranasal route is a reliable way to administer preanaesthetics and sedatives to children. Midazolam has been accepted as a safe and effective intranasal premedication. Intranasal dexmedetomidine, a well-tolerated and convenient treatment option, has been shown to induce a favorable anxiolysis in children